ANALISIS STRATEGI PEMASARAN PADA PERUSAHAAN PRODUK BERAS ROSITA DI KEDIRI JAWA TIMUR - Anto Rujianto (Program Studi Manajemen, 2019)
In formulating its business strategy, the company must be clear and the selected strategy must be in accordance with the vision, mission, competence and excellence which are owned by the company. The analytical tool used to evaluate express and measure events or trends that occur outside the company is a matrix evaluation of external factors (EFE) which generates opportunities and threats, in an organization, so that it can formulate strategies to take advantage of opportunities and avoid or mitigate the impact of threats. To analyze the competition, the company carried out five forces model of competition. While the internal factor evaluation matrix (IFE) is used to evaluate, express and measure events or trends that occur inside the company such as the strengths and weaknesses of the company; then it carried out a SWOT analysis (Strength, Weakness, Opportunity, Threat) which is a series combination of external analysis and internal analysis, thus allowing known about alternatives to the strategy obtained. Based on the analysis results which are conducted by using Michael Porter's model of five powers, it indicated that the rice supply in Kediri industry is still attractive. It is characterized by the value of interest based on the analysis of competition in the industry in the high category, the Rice Products Company “Rosita” have to constantly do a competition to gain market position with efforts to give priority to quality competition, product and price to improve service or satisfaction guarantee. Given the area known as the East Java area of ​​a large agricultural producer; it is a great opportunity in obtaining these benefits, it must be addressed by the businesses by formulating and implementing a reliable strategy in an effort to win the competition